Analysis Of The Speech Patterns Of Said Patients And Their Causes On Arabic Language Speaking Skills - Muin, Muhamad Fatkhul; Mukarromah, Khafidatul; Suhardi, Reza Fachrial (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
This research aims to analyze the speech patterns of people with slurs (dysarthria) and their causes in Arabic speaking skills. The method used is naturalistic qualitative with a case study approach to people with lisp (dysarthria). Data was collected through listening-writing and recording techniques. The results of this study show that the speech patterns of people with a lisp have an influence on Arabic speaking skills. This is because the sound of the letters produced in hijaiyah letters is similar to the alphabet. Disorders experienced by lisp sufferers are generally caused by hereditary factors and short tongues.